Tinjauan Hukum Pembubaran Perseroan Terbatas Atas Keputusan Rapat Umum Pemegang Saham (RUPS) Sesuai dengan Aturan Hukum Indonesia dan Malaysia - Paramadani, Salsabila Putri (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The dissolution of a limited liability company is also very dependent on the actions of the GMS which is the highest organ in a limited liability company in making company decisions that will determine the directors in taking the direction of company policy in dissolving the company, this is because the directors are still bound and bear legal consequences if the mechanism for dissolving the company is carried out in an incorrect manner and violates the provisions of the law. The problem in this study is related to the company that does not have assets at the time of dissolution and compared with the legal rules of dissolution of the company in Indonesia with those in Malaysia. The method in this research is normative juridical. The results of this study indicate that there are some similarities and differences in the process of dissolution of a limited liability company according to legal provisions in Indonesia and Malaysia which are ASEAN countries, this is because the legal system used by Indonesia adheres to the civil law legal system, while Malaysia is common law.